Isolated Fe-Co heteronuclear diatomic sites as efficient bifunctional catalysts for high-performance lithium-sulfur batteries - Sun, Xun; Qiu, Yue; Jiang, Bo; Chen, Zhaoyu; Zhao, Chenghao; Zhou, Hao; Yang, Li; Fan, Lishuang; Zhang, Yu; Zhang, Naiqing (Nature communications, 2023)
The slow redox kinetics of polysulfides and the difficulties in decomposition of Li 2 S during the charge and discharge processes are two serious obstacles to the practical application of lithium-sulfur batteries. Herein, we construct the Fe-Co diatomic catalytic materials supported by hollow carbon spheres to achieve high-efficiency catalysis for the conversion of polysulfides and the decomposition of Li 2 S simultaneously. The Fe atom center is beneficial to accelerate the discharge reaction process, and the Co atom center is favorable for charging process. Theoretical calculations combined with experiments reveal that this excellent bifunctional catalytic activity originates from the diatomic synergy between Fe and Co atom. As a result, the assembled cells exhibit the high rate performance (the discharge specific capacity achieves 688 mAh g −1 at 5 C) and the excellent cycle stability (the capacity decay rate is 0.018% for 1000 cycles at 1 C). The slow redox kinetics of polysulfides and the difficulties in decomposition of Li 2 S are two serious obstacles to lithium-sulfur batteries. Here, the authors report an isolated Fe-Co heteronuclear diatomic catalyst to achieve high efficiency bifunctional catalysis for lithium-sulfur batteries.